ANALISIS PENGEMBANGAN POTENSI EKONOMI DI KALIMANTAN BARAT TAHUN 2014 - 2017 - Raden Ajeng Lia Susilawati; Zainal Arifin; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2019)
Regional development planning is something that must be considered and carried out periodically by looking at several aspects related to regional development. One important thing to note is the economic potential of the area. West Kalimantan Province is one of the provinces that has potential natural resources to be developed. However, it needs to be considered further, this is because development that focuses on the natural sector as a primary will have an impact on the weak competitiveness of the human resource sector. This study aims to analyze the leading sectors of the Province of West Kalimantan 2014-2017 and analyze the economic sectors that have the potential to be developed to support the economic growth of the Province of West Kalimantan. This study uses secondary data taken from the Central Statistics Agency (BPS) of West Kalimantan. Data analysis methods used in this study are Shift Share and Location Quotient. The Location Quotient results show that the leading sectors in the Province of West Kalimantan from 2014 to 2017 were Agriculture, Forestry and Fisheries, the Information and Communication sector, the Real Estate sector, the Government Administration sector, the Mandatory Social Security and Mandatory Social Security sector and the Health Services and Social Activities sector. While the shift share is known that the entire sector is a potential sector to be developed except the Agriculture, Forestry and Fisheries sectors..